Fogo e fauna: o que sabemos? Revisão bibliográfica sobre os efeitos do fogo nos principais grupos animais do cerrado - Castro, Júlia Castelli [UNESP] (2019)
Fire is an agent of wide natural occurrence in tropical savannas, responsible for transformations in animals communities and vegetation structure. In the Cerrado, natural fire occurs during the transition from the dry season to the wet season. Transformations created by fire produce mosaics of phytophysiognomies that promote and maintain the biodiversity of the environment. Intensity, frequency and extensions of burned area are important factors of knowledge over the fire regime, mainly, to evaluate the effects of anthropogenic burnings. Despite its major importance, little is known about effects of fire in animals communities, whether of natural or anthropic origin. Aspects such as animal behavior and morphology directly interfere on the susceptibility degree on each group, because fire events cause physical changes in environment, promoting variation in habitats of some animals, modificating the availability of resources, refuges and nesting sites. This study evaluate, by reviewing the literature, the effects of fire in several animal groups, with the objective of organizing their effects into positive, negative or neutral for each group. We show that some species are highly adapted to fire, taking refuge underground and benefiting from the post fire environment. However, other species can be eliminated from those habitats